MONITORING OF SIDE EFFECTS OF ANTI-TUBERCULOSIS DRUGS ON THE CASES OF PULMONARY TB PATIENT IN CIKAMPEK PRIVATE HOSPITAL - Hidayah, Himyatul; Amal, Surya; Falahah (International Journal of Psychosocial Rehabilitation, 2020)
In Indonesia Tuberculosis (TB) is still a serious health problem and shows an increase in cases from year to year. West Java (0.7%) province with the highest pulmonary TB, given the increasing drug-related problems (Drug Related Problems) against antituberculosis drugs in the category of adverse drug reactions (Adverse Drug Reactins). This study aims to obtain information on the side effects of antituberculosis drugs experienced by patients with new cases of pulmonary TB in Cikampek Private Hospital. The research method is a prospective observational monitoring of drug side effects on a regular basis every week for 1 month of intensive treatment. The number of samples in this study were 83 patients. The results showed that the percentage of side effects of antituberculosis drugs experienced by TB sufferers during intensive treatment were red in the urine (100%), nausea (34.85%), spasms (27.27%), tingling (18.18%) , dizziness (25.76%) and no appetite (15.15%). Fisher's test analysis results showed that statistically the socio-demographic characteristics of the respondents evaluated did not affect the incidence of ADRs, but clinically there was a significant relationship.